Web-based English grammar system for personalized learning - Yan, Qian Ping (2016)
The Primary School Leaving Examination (PSLE) is a national examination taken by all Primary Six students in Singapore. It is critical that students do well for this examination as it determines the next phase of their life. English Language is an important role as it acts as the bridge with the other English-speaking world. Grammar, being the basic foundation of English, is mainly emphasized in PSLE English Language. With the huge advancements in technology in this era, e-learning solutions are gaining noticeable popularity as a result. With e-learning, students are able to study at their own convenience and comfort. This report focuses on the web based e-learning system that is built to allow students, especially Primary Six students, to learn and practice grammar in preparation for their PSLE English examination. It focuses on the different grammar sections such as Grammar MCQ, Grammar Cloze, Synthesis and Transformation, and as well as Editing for Spelling and Grammar. The learning concepts defined for each section and questions in this system were gathered from the past year exam papers and assessment books. Grammar Express allows students to search for questions, learn concepts for each section, practice questions on the sections that they are weak at, and take a paper test with a time limit. Students are also encouraged to improve their learning experience through forums. In addition, the learning system is able to keep track of the student’s usage. The functions mentioned above are discussed in detail in the rest of this report, along with the future developments.